1978
DOI: 10.1128/aem.35.4.679-684.1978
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial oxidation of polyethylene glycol

Abstract: The metabolism of polyethylene glycol (PEG) was investigated with a synergistic, mixed culture of Flavobacterium and Pseudomonas species, which are individually unable to utilize PEGs. The PEG dehydrogenase linked with 2,6dichlorophenolindophenol was found in the particulate fraction of sonic extracts and catalyzed the formation of a 2,4-dinitrophenylhydrazine-positive compound, possibly an aldehyde. The enzyme has a wide substrate specificity towards PEGs: from diethylene glycol to PEG 20,000. Km values for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 9 publications
1
38
0
1
Order By: Relevance
“…The fact that only one hydroxyl group was attacked and other remained intact gets support from stoichiometry of the reaction as well. Literature survey shows that similar types of oxidative products were reported [20][21][22][24][25][26] .…”
Section: Product Analysissupporting
confidence: 53%
“…The fact that only one hydroxyl group was attacked and other remained intact gets support from stoichiometry of the reaction as well. Literature survey shows that similar types of oxidative products were reported [20][21][22][24][25][26] .…”
Section: Product Analysissupporting
confidence: 53%
“…However, some studies found that PEG can be oxidized by enzymes and some proteins still adsorb on to it. 10,14,15 Natural products as bovine serum albumin (BSA) are also exploited to form a protective layer on the NPs to improve biocompatibility and transport of the NPs; 16 for instance, novel commercial drugs, such as Abraxane, incorporate albumin in the drug formulation to efficiently accumulate the drug in the tumor due to an enhanced permeability and retention and to reduce the risk of hypersensitivity reactions. Drug release in albumin carriers can be triggered naturally by protease digestion or pH-responsive systems; the payload can be tuned by the amount of albumin on the NPs, and the unfolding of the protein on the NP can facilitate their clearance by phagocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of Class 4 communities in which the community, but not its individual species, effects a concerted attack on the substrate, are abundant [see reviews by Bull (1980) and Bull & Slater (1982)l. Such communities have, for instance, been incriminated in the degradation of xenobiotics as diverse as poly(ethy1ene glycol) (Kawai et al, 1977) and nylon polymers (Kinoshita et al, 1975), linear alkylbenzene sulphonate detergents (Johanides & Hrsak, 1976), phenols such as orcinol (Osman et af., 1976), cyanideand acrylonitrile-containing wastes, herbicides such as pichloram (Lovatt er al., 1978), dalapon (Senior et af., 1976) and the related 2-chloropropionamide (Reanney et af., 1983).…”
Section: Nj Ukmentioning
confidence: 99%